Mycorrhizae: a key interaction for conservation of two endangered Magnolias from Andean forests (2019)
Background and aims – Magnolia species are highly endangered in neotropical forests where they are highly endemic and often very rare. However, little is known about their nutritional and soil conditions in natural forests. In this study, we focused on two endangered Magnolia species that cohabit in the Colombian Andean cloud forests in order to identify their conservation and nutritional status. We hypothesize that these species might exhibit mycorrhizal colonization that enhance nutrients uptake in poor and disturbed soils. Methods – Individuals of Magnolia jardinensis and M. yarumalensis were assessed in 11 000 m2 of Andean forests remnants from Jardín municipality (Antioquia, Colombia). Foliar and soil samples were analysed in the lab. Through a Principal Component Analysis (PCA) we identified the relationship between soil conditions and foliar nutrition. Root fragments and rhizosphere samples from seedlings and juveniles up to 3 m tall were collected to verify mycorrhizal colonization and presence of other microorganisms. Adults were excluded of the sampling due to the difficulties to differentiate their roots among the rest of the species in the forest fragments. Key results – The surveys show that the M. yarumalensis population has an inverted J-shaped diametric distribution suggesting a potential recovering population while the smaller overall distribution of M. jardinensis in all diametric categories suggests that this species is likely to become extinct. Both species grow in acidic, infertile soils, although foliar nutrient concentrations did not correlate with soil-nutrient availability. Such a discrepancy and the high colonization levels of mycorrhizae (60–70%) and dark septate endophytes (40–45%), suggest that plant-microorganisms may facilitate nutrition and enhance survival of Magnolia species in stressed environments. Other fungi and bacteria were also found in their rhizosphere, but their role with respect to Magnolia species remains unclear. Conclusions - Mycorrhizal colonization of endangered Magnolia species seems to play a key role to their performance in natural disturbed Andean forests. Aspects related to soil and rhizosphere ecology should be included in conservation projects for endangered and endemic plants. Key words – Rhizosphere, Andean cloud forests, Magnolia jardinensis, Magnolia yarumalensis, soil fertility, tree nutrition, conservation, mycorrhizae.